Paneth Cell Hyperplasia and Metaplasia in Hirschsprung-associated Enterocolitis in An Aganglionosis Rat Model - Iskandar Rahardjo Budianto; Agus Firmansyah; Yefta Moenadjat; Ahmad Aulia Jusuf; Vivian Soetikno (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Many hypotheses regarding the pathophysiology of enterocolitis in aganglionic megacolon or Hirschsprung disease (HSCR) has been proposed. Paneth cells are columnar intestinal epithelial cells that have an important role in maintaining of intestinal homeostasis as a bactericide. Since enterocolitis in HSCR may have association with Paneth cells metaplasia and hyperplasia, current study investigated Paneth cells metaplasia and hyperplasia in the sigmoid colon of HSCR rat model and its products, namely a-defensins and IL-1b, in the sigmoid colon tissues.METHODS: Aganglionosis-induced and control Sprague-Dawley rats were euthanized on Day (D)-7, -14, -17, -19, -21, -23, -25, and -28. Sigmoid colon tissue was isolated at each time point, and degree of enterocolitis as well as Paneth cells metaplasia and hyperplasia were analyzed by Hematoxylin-eosin staining, then protein levels of a-defensins and interleukin (IL)-1b were determined by enzyme-linked immunosorbent assay (ELISA).RESULTS: Enterocolitis scores increased with time. The Paneth cells metaplasia and hyperplasia were observed on D14 until D28 (p<0.01 vs. control group) followed by an increased in the levels of IL-1b. The levels of a-defensins protein expression were initially increased (D7-D14; p<0.01 vs. control group) but then undergo reciprocal changes on D19 until D28 (p<0.01 vs. D7 and D14). Positive correlations between the degree of enterocolitis and Paneth cells number were detected in the sigmoid colon (r=0.42).CONCLUSION: Paneth cells underwent metaplasia and hyperplasia in the sigmoid colon of HSCR rats corresponding to an increase in the degree of enterocolitis, but not followed by an increase in the level of a-defensins as well as IL-1b, suggesting that there is an involvement of Paneth cells in the pathophysiology of enterocolitis due to HSCR.KEYWORDS: Hirschsprung, enterocolitis, defensins; metaplasia, Paneth cell, animal model